A preferred AMPK phosphorylation site adjacent to the inhibitory loop of cardiac and skeletal troponin I - Sancho Solis, Raquel (Wiley Subscription Services, Inc., A Wiley Company, 2011)
5′-AMP-activated protein kinase (AMPK) is a serine/threonine protein kinase that is activated when cellular AMP to ATP ratios rise, potentially serving as a key regulator of cellular energetics. Among the known targets of AMPK are catabolic and anabolic enzymes, but little is known about the ability of this kinase to phosphorylate myofilament proteins and thereby regulating the contractile apparatus of striated muscles. Here, we demonstrate that troponin I isoforms of cardiac (cTnI) and fast skeletal (fsTnI) muscles are readily phosphorylated by AMPK. For cTnI, two highly conserved serine residues were identified as AMPK sites using a combination of high-resolution top-down electron capture dissociation mass spectrometry, (32)P-incorporation, synthetic peptides, phospho-specific antibodies, and site-directed mutagenesis. These AMPK sites in cTnI were Ser149 adjacent to the inhibitory loop and Ser22 in the cardiac-specific N-terminal extension, at the level of cTnI peptides, the intact cTnI subunit, whole cardiac troponin complexes and skinned cardiomyocytes. Phosphorylation time-course experiments revealed that Ser149 was the preferred site, because it was phosphorylated 12–16-fold faster than Ser22 in cTnI. Ser117 in fsTnI, analogous to Ser149 in cTnI, was phosphorylated with similar kinetics as cTnI Ser149. Hence, the master energy-sensing protein AMPK emerges as a possibly important regulator of cardiac and skeletal contractility via phosphorylation of a preferred site adjacent to the inhibitory loop of the thin filament protein TnI.